The Role of Endothelial Dysfunction in the Pathogenesis of Pregnancy-Related Pathological Conditions: A Review - Curakova Ristovska, Elena; Genadieva Dimitrova, Magdalena; Todorovska, Beti; Milivojevic, Vladimir; Rankovic, Ivan; Samardjiski, Igor; Bojadzioska, Maja (Walter de Gruyter GmbH, 2023)
In the recent decades, endothelial dysfunction (ED) has been recognized as a significant contributing factor in the pathogenesis of many pathological conditions. In interaction with atherosclerosis, hypercholesterolemia, and hypertension, ED plays a crucial role in the pathogenesis of coronary artery disease, chronic renal disease, and microvascular complications in diabetes mellitus. Although ED plays a significant role in the pathogenesis of several pregnancy-related disorders such as preeclampsia, HELLP syndrome, fetal growth restriction, and gestational diabetes mellitus, the exact pathogenetic mechanisms are still a matter of debate. The increased prevalence of these entities in patients with preexisting vascular diseases highlights the essential pathological role of the preexisting ED in these patients. The abnormal uteroplacental circulation and the release of soluble factors from the ischemic placenta into the maternal bloodstream are the main causes of the maternal ED underlying the characteristic preeclamptic phenotype. Besides the increased risk for maternal and fetal poor outcomes, the preexisting ED also increases the risk of development of future cardiovascular diseases in these patients. This study aimed to look deeper into the role of ED in the pathogenesis of several pregnancy-related hypertensive and liver diseases. Hopefully, it could contribute to improvement of the awareness, knowledge, and management of these conditions and also to the reduction of the adverse outcomes and additional long-term cardiovascular complications.
Keywords: endothelial dysfunction; hypertensive disorders of pregnancy; gestational hypertension; preeclampsia; HELLP Syndrome; acute fatty liver of pregnancy